Variable transmittance optical laminate, method for manufacturing same, and smart window including same
By adjusting the compression elastic modulus ratio and content of the spacer in the variable transmittance optical laminate, the problems of fixed transmittance and insufficient durability of traditional glass windows are solved, and the durability and light transmittance are improved. Suitable for smart windows and transportation.
Patent Information
- Application Number
- CN202380043867.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-04-20
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The glass window transmission of traditional mobile tools is fixed, which may cause drivers to find it difficult to view the surrounding conditions or be dizzy under different light conditions. The durability and quality of existing variable transmittance optical stacks are insufficient, making it easy to Cracked or scratches appear.
In the optical laminate with variable transmission, by including a spacer between the first laminate and the second laminate, the compression elastic modulus of the spacer and the compression elastic modulus of the laminate are from 0.75 to 1.55, and the interval is from 0.75 to 1.55. The content of the product is 0.5 to 3.0% by weight to ensure uniformity of the liquid crystal space and smooth light transmission, and avoid cracks and adverse phenomena.
It realizes an excellent durability of optical laminated bodies without cracks, ensures smooth light transmission and excellent quality, simplifies the production process, and is suitable for smart windows and transportation fields.
Smart Images

Figure CN119301513A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a variable transmittance optical stack, a method for manufacturing the same, and a smart window comprising the same. Background Art
[0002] Generally speaking, glass windows of mobile tools such as vehicles are often coated with external light blocking coatings. However, the transmittance of glass windows of conventional mobile tools is fixed, and the transmittance of external light blocking coatings is also fixed. Therefore, since the overall transmittance of the windows of such conventional mobile tools is fixed, accidents may occur. For example, if the overall transmittance is set low, then although there is no problem during the day when the surrounding light is sufficient, in the case of insufficient surrounding light at night, it is difficult for the driver to correctly view the surrounding conditions of the mobile tool. In addition, if the overall transmittance is set high, there is a problem that the driver may be dazzled during the day when the surrounding light is sufficient. For this reason, a variable transmittance optical laminate that can change the transmittance of light when a voltage is applied has been developed.
[0003] The above-mentioned variable transmittance optical laminate is driven in a variable transmittance manner by applying voltage to drive the liquid crystal. The variable transmittance optical laminate developed so far is produced by forming a conductive layer for driving the liquid crystal on a separate substrate and then combining it with other elements such as a polarizing plate.
[0004] Korean registered patent gazette No. 10-2226630 discloses a dimming film, bonding glass and a method for manufacturing a dimming film, wherein the dimming film supports a liquid crystal layer by sandwiching a first and a second stack having an orientation film, and controls the orientation of liquid crystal molecules in the liquid crystal layer and controls transmitted light by driving electrodes provided on the first and second stacks, wherein a spacer is provided to maintain the thickness of the liquid crystal layer, the Vickers hardness value Xs of the spacer is greater than 16.9 and less than 40.2, and the Vickers hardness value Xf of the second stack is greater than 11.8 and less than 35.9.
[0005] However, there is a problem that defects may occur due to the correlation between the hardnesses of the stack and the spacer even within the same numerical range, which may result in fatal problems in the durability and quality of the device.
[0006] Therefore, the actual situation is that it is necessary to develop a durable variable transmittance optical stack that can suppress interference between substrates by revealing the correlation between the compressive elastic modulus between the stack and the spacer, so that cracks or scratches are not generated, and the liquid crystal gap can be uniformly maintained. Summary of the invention
[0007] Technical issues
[0008] In order to solve the above-mentioned problems, the object of the present invention is to include a spacer in a dispersed liquid crystal arranged between a first stack and a second stack, wherein the ratio of the compressive elastic modulus of the above-mentioned spacer to the compressive elastic modulus of any one of the above-mentioned first stack and the second stack is 0.75 to 1.55, and the spacer content is 0.5 to 3.0 weight % relative to the total weight of the dispersed liquid crystal.
[0009] Another object of the present invention is to prevent cracks from occurring in an optical layered body.
[0010] Another object of the present invention is to ensure a liquid crystal space between the above-mentioned stacked bodies to facilitate light transmission.
[0011] However, the problems to be solved by the present invention are not limited to the problems mentioned above, and a person skilled in the art should be able to clearly understand other problems not mentioned based on the following description.
[0012] Solution to the problem
[0013] The present invention relates to a variable transmittance optical stack, which comprises: a first stack, which is stacked with a first polarizing plate, a first transparent conductive layer and a first orientation film in sequence; a second stack, which is stacked with a second polarizing plate, a second transparent conductive layer and a second orientation film in sequence; and a dispersed liquid crystal, which is arranged between the first stack and the second stack, wherein the dispersed liquid crystal contains a spacer, the ratio of the compressive elastic modulus of the spacer to the compressive elastic modulus of any one of the first stack and the second stack is 0.75 to 1.55, and the content of the spacer is 0.5 to 3.0 weight % relative to the total weight of the dispersed liquid crystal.
[0014] In the first aspect of the present invention, the compressive elastic modulus of either the first stack or the second stack may be 3,000 to 4,000 MPa.
[0015] In a second aspect of the present invention, the compressive elastic modulus of the spacer may be 2,000 to 5,500 MPa.
[0016] In a third aspect of the present invention, the spacer may include at least one selected from the group consisting of ball spacers and column spacers.
[0017] In a fourth aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may be formed to be in direct contact with one of the first polarizing plate and the second polarizing plate.
[0018] In a fifth aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may include one or more selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires.
[0019] In a sixth aspect of the present invention, at least one of the first polarizing plate and the second polarizing plate may include one or more selected from the group consisting of a functional coating layer, a protective layer, a phase difference adjusting layer, a refractive index adjusting layer, and an overcoat layer.
[0020] In a seventh aspect of the present invention, at least one of the first polarizing plate and the second polarizing plate may have a thickness of 30 to 200 μm.
[0021] In an eighth aspect of the present invention, a sealant may be provided between the first stack and the second stack.
[0022] In a ninth aspect of the present invention, the variable transmittance optical layered body may further include one or more selected from the group consisting of an adhesive / bonding layer, an ultraviolet absorbing layer, and an impact-resistant layer.
[0023] Furthermore, the present invention relates to a method for producing the variable transmittance optical layered body.
[0024] Furthermore, the present invention relates to a smart window including the variable transmittance optical stack.
[0025] Furthermore, the present invention relates to a vehicle comprising the above-mentioned smart window.
[0026] In addition, the present invention relates to a car in which the above-mentioned smart window is applied to more than one of a front window, a rear window, a side window, a sunroof and an interior partition.
[0027] In addition, the present invention relates to a wearable device comprising the above-mentioned smart window.
[0028] Furthermore, the present invention relates to a building window comprising the above-mentioned smart window.
[0029] Effects of the Invention
[0030] According to the variable transmittance optical stack of the present invention, when the ratio of the compressive elastic modulus of the above-mentioned spacer to the compressive elastic modulus of any one of the first stack and the second stack satisfies 0.75 to 1.55, and the spacer content satisfies 0.5 to 3.0 weight % relative to the total weight of the dispersed liquid crystal, an optical stack that does not generate cracks and has excellent durability can be provided.
[0031] Furthermore, according to the variable transmittance optical layered body of the present invention, light can be smoothly transmitted through the liquid crystal space with less occurrence of defects, and thus can exhibit characteristics with excellent reliability.
[0032] Furthermore, according to the variable transmittance optical layered body of the present invention, the liquid crystal space between the first layered body and the second layered body is uniformly ensured, so that an optical layered body with excellent quality can be provided.
[0033] Furthermore, the variable transmittance optical layered body of the present invention can omit the steps of forming a conductive layer on a substrate and bonding it to other members, which is a conventional method for forming an optical layered body. Therefore, the production process can be simplified compared with conventional optical layered bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The diagram shows a stacked structure of a variable transmittance optical stack according to an embodiment of the present invention.
[0035] Figure 2 The diagram shows a stacked structure of polarizing plates included in a variable transmittance optical stack according to an embodiment of the present invention.
[0036] Figure 3 The diagram shows a stacked structure of a smart window for a vehicle according to an embodiment of the present invention.
[0037] Figure 4 The diagram illustrates the stacked structure of a smart window for a building according to one embodiment of the present invention.
[0038] Figure 5 The diagram illustrates the stacked structure of a smart window for building use according to another embodiment of the present invention.
[0039] The meanings of the symbols in the accompanying drawings are as follows:
[0040] 100: Polarizing plate
[0041] 110: Polarizer
[0042] 120: Functional coating
[0043] 130: Protective layer
[0044] 140: Adhesive / bonding layer
[0045] 200: Transparent conductive layer
[0046] 300: Dispersed liquid crystal
[0047] 400: Spacer
[0048] 500: Oriented film
[0049] 600: Adhesive / adhesive layer
[0050] 700: Smart window glass for vehicles
[0051] 800: Smart window glass for building windows. DETAILED DESCRIPTION
[0052] The present invention relates to a variable transmittance optical stack, a method for manufacturing the same, and a smart window comprising the same. The ratio of the compressive elastic modulus of the spacer of the variable transmittance optical stack to the compressive elastic modulus of any one of the first stack and the second stack satisfies the range of 0.75 to 1.55, and the spacer content satisfies the range of 0.5 to 3.0 weight % relative to the total weight of the dispersed liquid crystal, so that the optical stack does not produce cracks, the liquid crystal space between the first stack and the second stack is ensured to ensure smooth light transmission, and the occurrence of liquid crystal defects is reduced and the reliability is excellent.
[0053] In more detail, it relates to a variable transmittance optical stack, which includes: a first stack, which is stacked with a first polarizer, a first transparent conductive layer and a first orientation film in sequence; a second stack, which is stacked with a second polarizer, a second transparent conductive layer and a second orientation film in sequence; and a dispersed liquid crystal, which is arranged between the above-mentioned first stack and the second stack, wherein the above-mentioned dispersed liquid crystal contains a spacer, and the ratio of the compressive elastic modulus of the above-mentioned spacer to the compressive elastic modulus of any one of the above-mentioned first stack and the second stack is 0.75 to 1.55, and the content of the above-mentioned spacer is 0.5 to 3.0 weight% relative to the total weight of the dispersed liquid crystal.
[0054] In the past, the defectiveness of an optical laminate was evaluated by considering the hardness of the spacer and the laminate contained in the optical laminate, but even if the defectiveness was evaluated based on the hardness of the spacer and the laminate, there was still a problem of some defects. To this end, the present invention provides a variable transmittance optical laminate, which is not determined by the hardness of the spacer and the laminate in contact with it, but by the ratio of the compressive elastic modulus of the spacer to the laminate satisfying a predetermined range, specifically, the ratio of the compressive elastic modulus of the spacer to the compressive elastic modulus of the laminate satisfies 0.75 to 1.55, and the spacer content satisfies a predetermined range, specifically, 0.5 to 3.0 weight % relative to the total weight of the dispersed liquid crystal, so that cracks are not generated, and the incidence of liquid crystal screen defects such as streaks is significantly reduced.
[0055] In one embodiment of the present invention, the compressive elastic modulus of any one of the first stack and the second stack may be 3,000 to 4,000 MPa, and the compressive elastic modulus of the spacer may be 2,000 to 5,500 MPa. When the compressive elastic modulus of the stack and the spacer meet the above range, not only can the cracks of the optical stack and the poor performance of the liquid crystal screen be prevented, but also the driving stability of the optical stack can be advantageous.
[0056] The variable transmittance optical laminate of the present invention is particularly suitable for the technical field in which the transmittance of light can be changed by application of voltage, and can be used, for example, in smart windows and the like.
[0057] The so-called smart window refers to an optical structure that changes the transmittance of light according to the application of an electrical signal to control the amount of light or heat passing through. In other words, a smart window can change to a transparent, opaque or semi-transparent state according to voltage, and is also called variable transmittance glass, dimming glass or smart glass.
[0058] Smart windows can be used as partitions for dividing the interior space of vehicles and buildings or as partitions for privacy protection, or as skylights arranged in the openings of buildings. They can be used as highway signs, billboards, scoreboards, clocks or advertising screens, and can replace the glass of transportation vehicles such as windows or skylights such as cars, buses, airplanes, ships or trains.
[0059] The variable transmittance optical laminate of the present invention can also be used as a smart window in the above-mentioned technical fields, but because the conductive layer is directly formed on the polarizing plate and does not include a separate substrate for forming the conductive layer, the thickness is thin, which is beneficial to the bending characteristics, and can be particularly suitable for use in smart windows for vehicles or buildings. In one or more embodiments, the smart window using the variable transmittance optical laminate of the present invention can be used in transportation tools, such as the front window, rear window, side window and skylight of a car, or a building window, etc. In addition to the purpose of blocking external light, it can also be used for the internal space division of cars or buildings, etc. or privacy protection purposes, such as internal partitions, etc., and can also be used in wearable devices such as helmets, glasses or watches.
[0060] Hereinafter, the embodiments of the present invention will be described in more detail with reference to the accompanying drawings. However, the following drawings attached to this specification are only examples of preferred embodiments of the present invention, which serve to further understand the above-mentioned invention content and the technical concept of the present invention, so the present invention should not be interpreted only in accordance with the matters recorded in these drawings.
[0061] The terms used in this specification are intended to illustrate the embodiments and are not intended to limit the present invention. In this specification, unless otherwise specified in the context, the singular form also includes the plural form. For example, the "polarizing plate" used in this specification may refer to at least one of the first polarizing plate and the second polarizing plate, the "transparent conductive layer" may refer to at least one of the first transparent conductive layer and the second transparent conductive layer, the "functional coating" may refer to at least one of the first functional coating and the second functional coating, and the "alignment film" may refer to at least one of the first alignment film and the second alignment film.
[0062] The terms "comprises" and / or "comprising" used in this specification are used to mean that they do not exclude the existence or addition of one or more other constituent elements, steps, actions and / or elements other than the mentioned constituent elements, steps, actions and / or elements. Throughout the specification, the same reference numerals refer to the same constituent elements.
[0063] As illustrated in the accompanying drawings, spatially relative terms "below", "bottom", "lower", "above", "upper surface", "upper part", etc. can be used to easily describe the correlation between one element or constituent element and other elements or constituent elements. Spatially relative terms should be understood as terms that include different directions of the elements when in use or in operation in addition to the directions illustrated in the drawings. For example, when the elements illustrated in the drawings are turned over, the elements described as "below" or "lower" of other elements can be placed "above" other elements. Therefore, the exemplary term "below" can include both directions below and above. Elements can also be oriented in other directions, so spatially relative terms can be interpreted according to orientation.
[0064] The “top-view direction” used in the present specification may be interpreted as a direction perpendicular to the polarizing plate and / or the transparent conductive layer, that is, a direction viewed from the visible side of a user.
[0065] The term “substantially” as used in this specification may be interpreted not only as physically identical or identical but also as including the situation within the error range in the measurement or manufacturing process. For example, it may be interpreted as being within the error range of 0.1% or less.
[0066] Figure 1 is a diagram showing a stacked structure of a variable transmittance optical stack according to an embodiment of the present invention, Figure 2 2 is a diagram showing the stacked structure of the polarizing plates used in the above-mentioned variable transmittance optical stack. Figure 1 The variable transmittance optical laminate of the present invention may include a first polarizing plate 100-1, a second polarizing plate 100-2, a first transparent conductive layer 200-1, a second transparent conductive layer 200-2, a liquid crystal layer containing dispersed liquid crystals 300 and a spacer 400, a first alignment film 500-1, and a second alignment film 500-2.
[0067] Reference Figure 2 The polarizing plate 100 may include one or more selected from the group consisting of a functional coating 120, a protective layer 130 or an adhesive / bonding layer 140 on both sides with the polarizer 110 as the center, and may also include a phase difference adjustment layer (not shown), a refractive index adjustment layer (not shown), etc.
[0068] The polarizer 110 may be a conventional polarizer or a polarizer developed in the future. For example, a stretched polarizer or a coating polarizer may be used.
[0069] In one embodiment, the stretched polarizer may include a stretched polyvinyl alcohol (PVA) resin. The polyvinyl alcohol (PVA) resin may be a polyvinyl alcohol resin obtained by saponifying a polyvinyl acetate resin. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith may also be mentioned. As the other monomers mentioned above, unsaturated carboxylic acid series, unsaturated sulfonic acid series, olefin series, vinyl ether series, acrylamide series monomers having an ammonium group, etc. may be mentioned. In addition, the polyvinyl alcohol (PVA) resin includes modified substances, for example, polyvinyl formal or polyvinyl acetal modified by aldehydes may also be mentioned.
[0070] In one embodiment, the coating type polarizer may be formed by using a liquid crystal coating composition. In this case, the liquid crystal coating composition may include a reactive liquid crystal compound and a dichroic dye.
[0071] The reactive liquid crystal compound may refer to a compound containing a mesogen skeleton and one or more polymerizable functional groups. Such reactive liquid crystal compounds are widely known by the name of so-called reactive mesogens (RM). The reactive liquid crystal compound may be polymerized by light or heat to form a cured film having a polymer network while maintaining the liquid crystal arrangement.
[0072] The reactive liquid crystal compound may be a monofunctional or polyfunctional reactive liquid crystal compound. The monofunctional reactive liquid crystal compound may be a compound having one polymerizable functional group, and the polyfunctional reactive liquid crystal compound may be a compound having two or more polymerizable functional groups.
[0073] The above-mentioned dichroic dye is a component added to the liquid crystal coating composition to impart polarization characteristics, and has a property that the absorbance in the long axis direction of the molecule is different from the absorbance in the short axis direction. The above-mentioned dichroic dye can use a dichroic dye developed in the past or in the future, for example, it can include one or more selected from the group consisting of azo dyes (azo dyes), anthraquinone dyes (anthraquinone dyes), perylene dyes (perylene dyes), merocyanine dyes (merocyanine dyes), azomethine dyes (azomethine dyes), phthaloperylene dyes (phthaloperylene dyes), indigo dyes (indigodyes), dioxadine dyes (dioxadine dyes), polythiophene dyes (polythiophene dyes) and phenoxazine dyes (phenoxazine dyes).
[0074] The liquid crystal coating composition may further include a solvent capable of dissolving the reactive liquid crystal compound and the dichroic dye, for example, propylene glycol monomethyl ether acetate (PGMEA), methyl ethyl ketone (MEK), xylene, chloroform, etc. In addition, the liquid crystal coating composition may further include a leveling agent, a polymerization initiator, etc. within a range that does not hinder the polarization characteristics of the coating film.
[0075] The functional coating 120 is provided to improve the hardness of the polarizing plate 100 , and is not particularly limited as long as it can improve the hardness of the polarizing plate. For example, it may include a hard coating layer and / or a low refractive index layer.
[0076] The hard coating layer may be a hard coating layer developed in the past or in the future, and according to one embodiment of the present invention, may be formed from a hard coating composition including an acrylate or epoxy compound, inorganic particles, a photoinitiator, etc. The acrylate compound may include a monomer or oligomer containing a (meth)acrylate group, and the term "(meth)acryloyl-" used in this specification may be used to refer to "methacryloyl-", "acryloyl-", or both. Non-limiting examples of the acrylate compounds include neopentyl glycol acrylate, 1,6-hexanediol (meth)acrylate, propylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tetra(meth)acrylate, pentaglycerol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and the like. (Meth) acrylate, dipentaerythritol penta (meth) acrylate, dipentaerythritol tetra (meth) acrylate, dipentaerythritol hexa (meth) acrylate, tripentaerythritol tri (meth) acrylate, tripentaerythritol hexa (meth) acrylate, bis (2-hydroxyethyl) isocyanurate di (meth) acrylate, hydroxyethyl (meth) acrylate, hydroxypropyl (meth) acrylate, hydroxybutyl (meth) acrylate, isooctyl (meth) acrylate, isodecyl (meth) acrylate, stearyl (meth) acrylate, tetrahydrofurfuryl (meth) acrylate, phenoxyethyl (meth) acrylate or isobornyl (meth) acrylate, etc. They can be used alone or in combination of two or more. The above-mentioned acrylate compound can include epoxy (meth) acrylate compounds and / or carbamate (meth) acrylate compounds. In addition, the above-mentioned epoxy compound can include a monomer or oligomer having at least one epoxy group in the molecule. The above-mentioned epoxy group can be an alicyclic epoxy group. The carbon number of the alicyclic ring contained in the above-mentioned epoxy group can be 3 to 7, for example, it can be an alicyclic epoxy group (cyclohexyl epoxy group) containing a cyclohexane ring. The above-mentioned alicyclic ring can also have a substituent. For example, the above-mentioned alicyclic ring can contain an alkyl substituent with a carbon number of 1 to 20. When the carbon number of the above-mentioned alkyl substituent is greater than 20, it may be disadvantageous in terms of curing speed. The above-mentioned alkyl substituent includes a straight chain type or a branched type. When it is a branched type, the carbon number can be 3 or more.
[0077] According to one embodiment of the present invention, in the method for manufacturing a hard coating film, the hard coating composition contains inorganic particles. According to one embodiment of the present invention, as the inorganic particles, inorganic particles with a particle size of nanometers can be used, for example, nanoparticles with a particle size of 100 nm or less, preferably 10 to 100 nm, and more preferably 10 to about 50 nm can be used. In addition, as the inorganic particles, for example, silicon dioxide particles, aluminum oxide particles, titanium oxide particles, or zinc oxide particles can be used.
[0078] By including the above-mentioned inorganic particles, the hardness of the hard coating film can be further improved. According to one embodiment of the present invention, the content of the above-mentioned inorganic particles can be 10 to 60 parts by weight, preferably 20 to 50 parts by weight, relative to 100 parts by weight of the above-mentioned hard coating composition. By including the above-mentioned inorganic particles in the above-mentioned range, the hardness improvement effect of the hard coating film brought about by the addition of inorganic particles can be achieved within the range without reducing the physical properties of the hard coating composition.
[0079] According to one embodiment of the present invention, in the method for manufacturing a hard coating film, the hard coating composition includes a photoinitiator. According to one embodiment of the present invention, as the photoinitiator, 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, methyl benzoylformate, α,α-dimethoxy-α-phenylacetophenone, 2-benzoyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide or bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide can be cited, but it is not limited thereto. In addition, currently commercially available products include Irgacure 184, Irgacure 500, Irgacure 651, Irgacure 369, Irgacure 907, Darocur 1173, Darocur MBF, Irgacure 819, Darocur TPO, Irgacure 907, Esacure KIP 100F, etc. These photoinitiators may be used alone or in combination of two or more different ones.
[0080] According to one embodiment of the present invention, the content of the photoinitiator can be 0.5 to 10 parts by weight, preferably 1 to 5 parts by weight, relative to 100 parts by weight of the hard coating composition. When the photoinitiator is within the above range, sufficient cross-linking photopolymerization can be achieved without reducing the physical properties of the hard coating film.
[0081] In addition, in the method for producing a hard coating film of the present invention, in addition to the above-mentioned components, the hard coating composition may further contain additives commonly used in the technical field to which the present invention belongs, such as surfactants, anti-yellowing agents, leveling agents, or antifouling agents. In addition, the content thereof can be variously adjusted within the range that does not reduce the physical properties of the hard coating composition of the present invention, and therefore is not particularly limited.
[0082] The low refractive index layer is also provided to improve the hardness of the polarizing plate within the scope of the purpose of the present invention. The low refractive index layer may include one or more low refractive index agents selected from the group consisting of, for example, SiO2, Al2O3, MgF2, CaF and cryloite, and in some embodiments, may include the compounds or resins used in the hard coating. The hard coating and the low refractive index layer may be used alone, and in some embodiments, may also be used in a multilayer structure.
[0083] like Figure 2 As shown, the functional coating 120 can be formed by directly contacting one side of the polarizer 110, but is not limited thereto. For example, when the polarizing plate includes a phase difference adjustment layer or a refractive index adjustment layer, the functional coating 120 can be formed on one side of the phase difference adjustment layer or the refractive index adjustment layer, thereby stacking the functional coating, the phase difference adjustment layer or the refractive index adjustment layer and the polarizer in sequence.
[0084] The functional coating 120 is preferably formed on the liquid crystal layer side of the polarizer 110 including the dispersed liquid crystal 300, that is, on the inner side of the polarizer 110. For example, the first protective layer 130-1, the first functional coating 120-1, the polarizer 110, the second protective layer 130-2, and the second functional coating 120-2 may be stacked in sequence. In this case, the functional coating has the advantage of being able to impart a hardness suitable for forming a transparent conductive layer or other components to the polarizer, thereby minimizing cracks or scratches generated during the manufacturing or processing steps of the optical laminate.
[0085] The Vickers hardness of the first functional coating 120 - 1 and the second functional coating 120 - 2 may be 18 to 41 respectively. The hardness of the first functional coating 120 - 1 and the second functional coating 120 - 2 may be the same, but not limited thereto, and each may have a different hardness.
[0086] The Vickers hardness can be measured using a Vickers tip of a nano indenter (HM500, Helmut Fishcher). When the Vickers hardness of the functional coating satisfies the above range, it can not only have excellent wear resistance, but also further improve the bending resistance or durability of the optical laminate. In more detail, it can more effectively suppress defects such as cracks in the conductive layer due to the pressure applied by the spacer or the chemical reaction of the liquid crystal, alignment film, etc. during the bonding process of the first laminate (upper laminate) and the second laminate (lower laminate).
[0087] In one or more embodiments, the thickness of the first functional coating 120-1 and the second functional coating 120-2 may be 1 to 30 μm, more preferably 1 to 20 μm. The thickness may refer to the thickness after drying. When the thickness of the first functional coating 120-1 and the second functional coating 120-2 meets the above range, the hardness is excellent and thinness can be achieved, and the bending resistance or durability can be further improved.
[0088] The protective layer 130 is intended to protect the polarization characteristics of the polarizer from being affected by subsequent processes and the external environment, and can be implemented in the form of a protective film or the like.
[0089] The protective layer may be formed by directly contacting one or both sides of the polarizer, but is not limited thereto. For example, the protective layer may be used in a multilayer structure in which more than one protective layer is continuously stacked, and may be formed by directly contacting other components such as a phase difference adjustment layer.
[0090] In one or more embodiments, the protective layer 130 may include one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), diacetyl cellulose, triacetyl cellulose (TAC), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyethyl acrylate (PEA), polyethyl methacrylate (PEMA) and cyclic olefin polymer (COP).
[0091] In addition, the protective layer 130 may further include an ultraviolet absorber on the outermost surface to prevent the function of the optical laminate from being reduced. The ultraviolet absorbing layer is not particularly limited as long as it is used to prevent the degradation of the optical laminate caused by ultraviolet rays. For example, salicylic acid ultraviolet absorbers (phenyl salicylate, p-tert-butyl salicylate, etc.), benzophenone ultraviolet absorbers (2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, etc.), benzotriazole ultraviolet absorbers (2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy- 3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2,2-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy- 3'-tert-butyl-5'-(2-octyloxycarbonylethyl)-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(1-methyl-1-phenylethyl)-5'-(1,1,3,3-tetramethylbutyl)-phenyl)benzotriazole, 2-(2H-benzotriazol-2-yl)-6-(linear and side chain dodecyl)-4-methylphenol, octyl-3-[3-tert-butyl-4-hydroxy-5-(chloro-2H-benzotriazol-2-yl)phenyl]propionate and 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy-5-( The invention also includes a mixture of cyanoacrylate-based UV absorbers (2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, etc.), triazine-based UV absorbers, etc., preferably a benzotriazole-based UV absorber or a triazine-based UV absorber which has high transparency and an excellent effect of preventing degradation of the polarizing plate or the transmittance variable layer, and particularly preferably a benzotriazole-based UV absorber having a more suitable spectral absorption spectrum. The above-mentioned benzotriazole-based ultraviolet absorber can also be a bis (Bis) substance, for example, it can be 6,6'-methylenebis (2-(2H-benzo [d] [1,2,3] triazol-2-yl) -4- (2,4,4-trimethylpentane-2-yl) phenol), 6,6'-methylenebis (2-(2H-benzo [d] [1,2,3] triazol-2-yl) -4- (2-hydroxyethyl) phenol), etc.
[0092] The polarizing plate 100 may further include an adhesive layer 140 to ensure uniform adhesion between substrates. The adhesive layer 140 may be formed using an adhesive or an adhesive. As the adhesive, a photocurable adhesive is preferably used.
[0093] The photocurable adhesive may be cross-linked and cured by exposure to active energy rays such as ultraviolet (UV) and electron beam (EB), thereby exhibiting strong adhesive force, and may be composed of reactive oligomers, reactive monomers, photopolymerization initiators, and the like.
[0094] The reactive oligomer is an important component that determines the properties of the adhesive, and forms a cured film by forming a polymer bond through a photopolymerization reaction. Examples of the reactive oligomer that can be used include polyester resins, polyether resins, polyurethane resins, epoxy resins, polyacrylic resins, silicone resins, and the like.
[0095] The reactive monomer acts as a crosslinking agent and diluent for the reactive oligomer and affects the adhesive properties. Examples of the reactive monomer include monofunctional monomers, polyfunctional monomers, epoxy monomers, vinyl ethers, cyclic ethers, and the like.
[0096] The photopolymerization initiator absorbs light energy to generate free radicals or cations, thereby initiating photopolymerization. A suitable photopolymerization initiator may be selected and used according to the photopolymerizable resin.
[0097] As long as the adhesive has adhesion and viscoelasticity, there is no particular restriction, but from the perspective of ease of acquisition, it is preferably an acrylic adhesive, for example, it may include a (meth) acrylate copolymer, a crosslinking agent, and a solvent. The crosslinking agent may use a crosslinking agent developed in the past or in the future, for example, it may include a polyisocyanate compound, an epoxy resin, a melamine resin, a urea resin, a dialdehyde, a hydroxymethyl polymer, etc., and preferably may include a polyisocyanate compound. The solvent may include a common solvent used in the field of resin compositions, for example, alcohol compounds such as methanol, ethanol, isopropanol, butanol, and propylene glycol methoxy alcohol may be used; ketone compounds such as methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, and dipropyl ketone; acetate compounds such as methyl acetate, ethyl acetate, butyl acetate, and propylene glycol methoxy acetate; cellosolve compounds such as methyl cellosolve, ethyl cellosolve, and propyl cellosolve; solvents such as hydrocarbon compounds such as hexane, heptane, benzene, toluene, and xylene. They may be used alone or in combination of two or more.
[0098] In one embodiment, the adhesive layer can be formed on one or both sides of the polarizer by lamination. In the polarizing plate, in order to ensure sufficient adhesion / adhesion force and minimize the thickness of the optical laminate, the adhesive layer can have a thickness of 0.01 to 50 μm, preferably 0.05 to 20 μm, and more preferably 0.1 to 10 μm.
[0099] The transparent conductive layer 200 is provided for driving the liquid crystal layer and can be formed by directly contacting the polarizing plate 100. Figure 1 As shown, the first transparent conductive layer 200-1 and the second transparent conductive layer 200-2 can each be formed by direct contact with the first polarizing plate 100-1 and the second polarizing plate 100-2. In the past, optical laminates used to manufacture smart windows and the like were manufactured by forming a conductive layer for liquid crystal driving on one side of a substrate and bonding the other side of the substrate to a polarizing plate. However, the variable transmittance optical laminate of the present invention is characterized in that a conductive layer is directly formed on one side of a polarizing plate without including a separate substrate for forming a conductive layer, thereby reducing the thickness of the laminate and improving the transmittance and bending characteristics in a light transmission mode. In one embodiment, the transparent conductive layer 200 can be formed by direct vapor deposition on one side of the polarizing plate 100. At this time, in order to improve the adhesion between the transparent conductive layer 200 and the polarizing plate 100, it can be formed by directly contacting the pre-treated surface of the polarizing plate 100 after pre-treatment such as corona treatment or plasma treatment is performed on one side of the polarizing plate 100. The above-mentioned pretreatment is not limited to corona treatment or plasma treatment, and a pretreatment process developed in the past or in the future can be used within the scope that does not impair the purpose of the present invention. In another embodiment, in order to improve the adhesion to the polarizing plate 100, the above-mentioned transparent conductive layer 200 can be formed by directly contacting the polarizing plate 100 through an easy-adhesion layer (not shown) provided on one side of the polarizing plate 100. The transmittance of the above-mentioned transparent conductive layer 200 relative to visible light is preferably 50% or more. For example, it can include one or more selected from the group consisting of transparent conductive oxides, metals, carbon-based substances, conductive polymers, conductive inks and nanowires, but is not limited thereto, and materials for transparent conductive layers developed in the past or in the future can be used. In addition, the above-mentioned conductive layer can be composed of a structure of more than two layers by combining the above-mentioned substances. For example, the above-mentioned conductive layer can reduce the reflectivity of the incident light and improve the transmittance by a two-layer structure including a metal layer and a transparent conductive oxide layer. Since the metal layer has a high reflectivity, it may reduce the visibility of the screen when used alone. However, by laminating the transparent conductive oxide layer, the reflectivity can be reduced and the transmittance can be improved.
[0100] More specifically, in one or more embodiments, the transparent conductive oxide may include one or more selected from the group consisting of indium tin oxide (ITO), indium zinc oxide (IZO), indium tin zinc oxide (IZTO), aluminum zinc oxide (AZO), gallium zinc oxide (GZO), fluorine tin oxide (FTO), and zinc oxide (ZnO). In addition, the metal may include one or more selected from the group consisting of gold (Au), silver (Ag), copper (Cu), molybdenum (Mo), aluminum (Al), platinum (Pt), palladium (Pd), chromium (Cr), titanium (Ti), tungsten (W), niobium (Nb), tantalum (Ta), vanadium (V), iron (Fe), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), palladium (Pd), neodymium (Nd), and alloys containing at least one of them, for example, may include silver-palladium-copper (APC) alloy or copper-calcium (CuCa) alloy. The carbon-based material may include one or more selected from the group consisting of carbon nanotubes (CNT) and graphene, and the conductive polymer may include one or more selected from the group consisting of polypyrrole, polythiophene, polyacetylene, poly(3,4-ethylenedioxythiophene) (PEDOT) and polyaniline, etc. The conductive ink may be an ink mixed with metal powder and a curable polymer binder, and the nanowire may be, for example, silver nanowire (AgNW).
[0101] In addition, the transparent conductive layer 200 can be formed by combining the above-mentioned substances and having a structure of more than two layers. For example, in order to reduce the reflectivity of the incident light and increase the transmittance, it can be formed by a two-layer structure including a metal layer and a transparent conductive oxide layer. The transparent conductive layer 200 can be formed by a method commonly used in the art, for example, a coating process such as spin coating, roller coating, rod coating, dip coating, gravure coating, curtain coating, die coating, spray coating, blade coating, kneader coating, etc.; a printing process such as screen printing, spray printing, inkjet printing, letterpress printing, gravure printing, lithography, etc.; an evaporation process such as in-mold labeling (IML) injection method and chemical vapor deposition (CVD), physical vapor deposition (PVD), plasma enhanced chemical vapor deposition (PECVD); a dry or wet plating process, etc., to select an appropriate process to form.
[0102] The dispersed liquid crystal 300 is contained in a liquid crystal layer that adjusts the transmittance of light incident from one or more directions according to an electric field to change the driving mode of the optical stack, and includes a spacer 400. For example, it can be located in a liquid crystal space provided by a sealant (not shown) and a spacer 400 provided between the first stack and the second stack. There is no particular limitation on the dispersed liquid crystal 300 as long as it is driven according to an electric field and can control the transmittance of light. Dispersed liquid crystals developed in the past or in the future can be used. For example, the contents of the reactive liquid crystal compounds of the coated polarizer can be similarly applied. There is no particular limitation on the liquid crystal driving method of the liquid crystal layer. For example, it can be driven by a twisted nematic (TN) mode, but in addition, it can also be driven by a super twisted nematic (STN) mode, a vertical alignment (VA) mode, etc.
[0103] The above-mentioned frame sealant (not shown) can be located between the first stack and the second stack in the non-active area. The frame sealant can play a role in combining the first stack and the second stack, and can ensure the space for the liquid crystal layer between the first stack and the second stack together with the spacer. The above-mentioned frame sealant is not particularly limited as long as it combines the stacks and ensures the space for the liquid crystal layer. The frame sealant developed in the past or in the future can be used. For example, a curable resin can be included as a base resin. As the above-mentioned base resin, a UV-curable resin or a thermosetting resin known in the art that can be used for a frame sealant can be used. The above-mentioned UV-curable resin can be a polymer of a UV-curable monomer. The above-mentioned thermosetting resin can be a polymer of a thermosetting monomer. As the base resin of the above-mentioned frame sealant, for example, an acrylate resin, an epoxy resin, a carbamate resin, a phenol resin or a mixture of the above-mentioned resins can be used. In one embodiment, the above-mentioned base resin can be an acrylate resin, and the above-mentioned acrylate resin can be a polymer of an acrylic monomer. The above-mentioned acrylic monomer can be, for example, a multifunctional acrylate. In another embodiment, the frame-sealing glue may further include a monomer component in the base resin. The monomer component may be, for example, a monofunctional acrylate. In the present specification, a monofunctional acrylate may refer to a compound having one acryloyl group, and a multifunctional acrylate may refer to a compound having two or more acryloyl groups. The curable resin may be cured by irradiation with ultraviolet rays and / or heating. The ultraviolet irradiation conditions or heating conditions may be appropriately implemented within the scope that does not impair the purpose of the present application. The frame-sealing glue may further include an initiator, such as a photoinitiator or a thermal initiator, as needed. The frame-sealing glue may be formed by a method commonly used in the art, for example, the frame-sealing glue may be applied to the periphery of the liquid crystal layer (i.e., the non-active area) using a glue applicator equipped with a nozzle.
[0104] The spacer 400 plays a role in maintaining the liquid crystal gap of the liquid crystal layer constantly, and may include at least one of a ball spacer and a column spacer. In terms of processability, a ball spacer is particularly preferred. The spacer 400 is included in the dispersed liquid crystal, and may be one or more. There is no particular limitation on the height thereof, as long as it is a height suitable for supporting the liquid crystal layer.
[0105] In one embodiment, the content of the spacer 400 may be 0.5 to 3.0 wt % relative to the total weight of the dispersed liquid crystal. When the content of the spacer meets the above range, it can have advantages not only in terms of user visibility and improving transmittance in the light transmission mode, but also in terms of significantly reducing the defects of the liquid crystal screen caused by cracks or streaks of the optical laminate.
[0106] The alignment film 500 is not particularly limited as long as it is used to impart alignment to dispersed liquid crystals, and may preferably include photo-alignment or photocurable polymers, etc. For example, the alignment film 500 may be prepared by coating an alignment film coating composition including a photo-alignment or photocurable polymer, a photopolymerization initiator, and a solvent, and curing the composition.
[0107] The photo-orientable or photo-curable polymer is not particularly limited, and cinnamate polymers, polyimide polymers, and the like can be used. For example, polyvinyl cinnamate (PVCi), polysiloxane cinnamate (PSCN), poly(ω(4-chalconyloxy)alkoxyphenyl maleimide), 6-FDA-HAB-Cl, and the like can be used. Polymers that can show orientation and are developed in the past or in the future can be used.
[0108] The alignment film 500 may include a recessed portion formed by the spacer 400 .
[0109] In one embodiment, in addition to the above components, the polarizing plate 100 may also include other components for assisting or enhancing the characteristics of the optical laminate, for example, it may also include a phase difference adjustment layer, a refractive index adjustment layer, etc. to further improve the optical characteristics.
[0110] The above-mentioned phase difference adjustment layer is intended to supplement the optical properties of the optical laminate, and can be implemented in the form of a phase difference film, etc., and a phase difference film developed in the past or in the future can be used. For example, a quarter wave plate (1 / 4 wave plate) or a half wave plate (1 / 2 wave plate) for delaying the phase of light can be used, and they can be used alone or in combination.
[0111] The phase difference adjustment layer may be formed by directly contacting one side of the polarizer, but is not limited thereto. For example, the phase difference adjustment layer may be formed by directly contacting one side of the protective layer, or may be formed by directly contacting one side of the refractive index adjustment layer.
[0112] The phase difference adjustment layer may be a stretched polymer film or a liquid crystal polymer film obtained by appropriately stretching a polymer film capable of imparting optical anisotropy.
[0113] In one embodiment, the above-mentioned polymer stretch film can use a polymer layer containing the following substances: polyolefins such as polyethylene (PE) or polypropylene (PP), cyclo olefin polymers (COP: cyclo olefin polymer) such as polynorbornene, polyvinyl chloride (PVC), polyacrylonitrile (PAN), polysulfone (PSU), acrylic resin (acryl resin), polycarbonate (PC), polyesters such as polyethyleneterephthalate (PET), polyacrylate, polyvinyl alcohol (PVA) or triacetyl cellulose (TAC) and other cellulose ester polymers, or copolymers of two or more monomers among the monomers forming the above-mentioned polymers, etc.
[0114] The method for obtaining the above-mentioned polymer stretch film is not particularly limited, for example, it can be obtained by stretching the above-mentioned polymer material after being molded into a film shape. The above-mentioned method of being molded into a film shape is not particularly limited, and can be molded into a film by known methods such as injection molding, sheet molding, blow molding, injection blow molding, inflation molding, extrusion molding, foam molding, and tape casting, or by secondary processing molding methods such as compression molding and vacuum molding. Among them, extrusion molding and tape casting are preferably used. At this time, for example, an extruder equipped with a T-shaped mold, a circular mold, etc. can be used to extrusion mold the unstretched film. In the case of obtaining a molded product by extrusion molding, a material that has been melt-mixed in advance with various resin components, additives, etc. can be used, and it is also possible to mold via melt mixing during extrusion molding. In addition, it is also possible to use a common solvent in various resin components, such as chloroform, dichloromethane and other solvents to dissolve various resin components, and then cast and dry and solidify, thereby casting the unstretched film.
[0115] For the above-mentioned polymer stretched film, the above-mentioned formed film can be uniaxially stretched along the machine flow direction (MD; Mechanical Direction, longitudinal or length direction), uniaxially stretched along the direction perpendicular to the machine flow direction (TD; Transverse Direction, transverse or width direction), and can also be stretched by a sequential biaxial stretching method of roller stretching and tenter stretching, a simultaneous biaxial stretching method based on tenter stretching, a biaxial stretching method based on tubular stretching, etc. to produce a biaxially stretched film.
[0116] The liquid crystal polymer film may include a reactive liquid crystal compound in a polymerized state. The reactive liquid crystal compound may be similarly applied to the reactive liquid crystal compound of the coating type polarizer.
[0117] In one or more embodiments, the thickness of the phase difference adjustment layer may be 10 to 100 μm in the case of a polymer stretched film, and may be 0.1 to 5 μm in the case of a liquid crystal polymer film.
[0118] The refractive index adjustment layer (not shown) is provided to compensate for the refractive index difference of the optical laminate caused by the transparent conductive layer 200, and can play a role in improving the visible characteristics by reducing the refractive index difference. In addition, the refractive index adjustment layer can also be provided to correct the color caused by the transparent conductive layer 200. On the other hand, in the case where the transparent conductive layer has a pattern, the refractive index adjustment layer can compensate for the transmittance difference between the pattern area where the pattern is formed and the non-pattern area where the pattern is not formed.
[0119] Specifically, the transparent conductive layer 200 is stacked adjacent to other components (e.g., polarizers, etc.) having a different refractive index from the transparent conductive layer 200. Due to the difference in refractive index with other adjacent layers, a difference in light transmittance may be induced. In particular, when the transparent conductive layer is patterned, the patterned area and the non-patterned area may appear different. Therefore, by including the refractive index adjustment layer, the refractive index can be compensated to reduce the difference in light transmittance of the optical laminate. In particular, when the transparent conductive layer is patterned, the patterned area and the non-patterned area will not appear different.
[0120] In one embodiment, the refractive index of the refractive index adjustment layer can be appropriately selected according to the materials of other adjacent components, preferably 1.4 to 2.6, more preferably 1.4 to 2.4. In this case, light loss caused by the huge refractive index difference between other components such as the polarizer and the transparent conductive layer 200 can be prevented.
[0121] The above-mentioned refractive index adjustment layer is not particularly limited as long as it can prevent the huge refractive index difference between other components such as the polarizer and the transparent conductive layer 200. The compounds used in the formation of the refractive index adjustment layer in the past or developed in the future can be used. For example, it can be formed by a refractive index adjustment layer forming composition containing a polymerizable isocyanurate compound.
[0122] In one embodiment, in addition to the above components, the polarizing plate 100 may further include other components for assisting or enhancing the characteristics of the polarizer. For example, in order to further improve the mechanical durability, it may further include an overcoat layer.
[0123] In one or more embodiments, the polarizing plate 100 may have a thickness of 30 to 200 μm, preferably 30 to 170 μm, and more preferably 50 to 150 μm. In this case, a thin optical laminate can be manufactured while maintaining the optical properties of the polarizing plate 100 .
[0124] The variable transmittance optical laminate of the present invention may further include other components within the scope of not impairing the purpose of the present invention, for example, it may further include an adhesive / bonding layer 600 (see Figures 3 to 5 ), and may further include an ultraviolet absorbing layer and an impact-resistant layer.
[0125] The above-mentioned adhesive / bonding layer 600 can be formed using an adhesive or a pressure-sensitive adhesive, preferably having appropriate adhesion to prevent peeling, bubbles, etc. when operating the optical laminate, while having transparency and thermal stability, and can have viscoelastic properties that can be applied to smart windows.
[0126] The adhesive and pressure-sensitive adhesive described in the description of the pressure-sensitive adhesive / pressure-sensitive adhesive layer 140 can be directly applied to the adhesive and pressure-sensitive adhesive, and thus the description thereof is omitted.
[0127] The thickness of the above-mentioned adhesive / bonding layer 600 can be appropriately determined according to the type of resin that acts as an adhesive / adhesive, the adhesive / bonding strength, the environment in which the adhesive / adhesive is used, etc. In one embodiment, in order to ensure sufficient adhesive / bonding force and minimize the thickness of the optical laminate, the above-mentioned adhesive / bonding layer can have the following thickness: in the case of an adhesive layer, it can be 0.1 to 500 μm, preferably 0.5 to 450 μm, and more preferably 1 to 400 μm thick; in the case of an adhesive layer, it can be 2 to 30 μm, preferably 3 to 20 μm, and more preferably 5 to 10 μm thick. In one embodiment, the above-mentioned adhesive / bonding layer 600 can be formed on one or both sides of the polarizing plate by lamination or vacuum bonding.
[0128] The ultraviolet absorbing layer is not particularly limited as long as it is used to prevent degradation of the optical laminate due to ultraviolet rays. The ultraviolet absorber described in the protective layer 130 of the polarizing plate 100 can be directly applied, and thus description thereof is omitted.
[0129] The impact-resistant layer is not particularly limited as long as it is located in the inner direction and has the function of mitigating the impact and preventing the internal substrate from being damaged when an impact is applied to the front of the window. It is preferably a material with a large tolerance for strain energy, for example, a thermoplastic resin with high toughness. Examples of such resins include polycarbonate resins, polyimide resins, polyamide resins, polyamide-imide resins, polyester resins, and the like. In addition, since the present invention is intended for use in a display device, it is preferred to use a resin with excellent light transmittance, preferably optically transparent.
[0130] Figure 3 1 is a diagram showing a laminated structure of a vehicle smart window to which a variable transmittance optical laminate according to an embodiment of the present invention is applied, Figure 4 1 is a diagram showing a stacked structure of a smart window for building windows to which a variable transmittance optical stack according to an embodiment of the present invention is applied, Figure 5 It is a diagram showing the stacked structure of a smart window for building windows according to another embodiment of the present invention.
[0131] Reference Figures 3 to 5In addition to the above-mentioned variable transmittance optical laminate, the present invention includes a smart window having the above-mentioned variable transmittance optical laminate, and includes a car in which the above-mentioned smart window is applied to at least one of a front window, a rear window, a side window, a skylight, and an interior partition, and a building window including the above-mentioned smart window. For example, a car including the smart window of the present invention can be joined to a vehicle glass 700 (see Figure 3 ), for example, after placing adhesive films and vehicle glass on both sides of the variable transmittance optical stack, a press machine is used to heat the glass at a temperature of 90°C and a vacuum state of about 1 bar for 10 to 20 minutes. The adhesive film may include an EVA film, a PVB film, etc. In addition, the variable transmittance optical stack may be formed on both sides (see Figure 4 ) or on one side (refer to Figure 5 ) Joining building windows (window glass) 800, can be manufactured by coating UV adhesive on both sides of the variable transmittance optical laminate and joining the window glass, and then UV curing. Figure 4 or Figure 5 The smart window product for windows of the same structure can also be manufactured by laminating window glass on one side of the variable transmittance optical laminate. Figure 4 or Figure 5 Smart window products for windows of the same structure.
[0132] In addition, in addition to this, the above-mentioned smart window can also be applied to vehicles and wearable devices generally used in the field.
[0133] Implementation
[0134] The following are specific examples of the present invention. However, the present invention is not limited to the examples disclosed below, and can be implemented in a variety of different ways. The examples are only provided to make the disclosure of the present invention complete and to fully inform the scope of the invention to those skilled in the art of the present invention. The present invention is defined only by the scope of the claims. Unless otherwise stated, "%" and "parts" are mass % and mass parts, respectively.
[0135] Manufacturing Example 1: Polarizing Plate Preparation
[0136] (1) Swelling treatment process
[0137] A polyvinyl alcohol film (stock film) with a thickness of 60 μm (manufactured by Kuraray Co., Ltd., trade name "Kuraraypoval film VF-PE#6000", average degree of polymerization 2400, saponification degree 99.9 mol%) was continuously unwound from a stock roll while being conveyed and immersed in a swelling bath filled with pure water at 20°C for 30 seconds. In this swelling treatment step, inter-roll stretching (uniaxial longitudinal stretching) was performed by generating a difference in peripheral speed between the nip rolls. The stretching ratio was set to 2.5 times based on the stock film.
[0138] (2) Dyeing process
[0139] Next, the film passed through the nip rollers was immersed in a dyeing bath at 30°C with a mass ratio of pure water / potassium iodide / iodine / boric acid of 100 / 2 / 0.01 / 0.3 for 120 seconds. In this dyeing treatment, inter-roll stretching (longitudinal uniaxial stretching) was performed by generating a difference in peripheral speed between the nip rollers. The stretching ratio was set to 1.1 times based on the film after the swelling treatment step.
[0140] (3) Cross-linking treatment process
[0141] Next, the film passed through the nip rollers was immersed in a first crosslinking bath at 56°C with a mass ratio of pure water / potassium iodide / boric acid of 100 / 12 / 4 for 70 seconds. Inter-roll stretching (longitudinal uniaxial stretching) was performed by causing a difference in peripheral speed between the nip rollers and the nip rollers provided between the first crosslinking bath and the second crosslinking bath. The stretching ratio was set to 1.9 times based on the film after the dyeing treatment step.
[0142] (4) Color correction process
[0143] Next, the cross-linked film was immersed in a second cross-linking bath having a mass ratio of potassium iodide / boric acid / pure water of 9 / 2.9 / 100 at 40° C. for 10 seconds.
[0144] (5) Cleaning process
[0145] Next, the membrane after the second crosslinking treatment was immersed in a cleaning bath filled with pure water at 14° C. for 5 seconds and rinsed with 5 ml 3 / h and elution temperature of 14°C for cleaning.
[0146] (6) Drying process
[0147] Next, the film after the washing treatment step was passed through a drying furnace to be heated and dried at 80° C. for 190 seconds to produce a polarizer film. The moisture content after drying was 13.6%, and the thickness of the obtained polarizer film was about 21 μm.
[0148] (7) Joining process
[0149] Next, as an adhesive, a water-based adhesive containing 5 parts by mass of polyvinyl alcohol relative to 100 parts by mass of water was prepared. Then, protective films were laminated on both sides of the polarizer film using the prepared UV adhesive. The obtained laminate was exposed to UV light to cure the adhesive, thereby manufacturing an upper polarizing plate and a lower polarizing plate, respectively. In addition, the thickness of the adhesive layer in the obtained polarizing plate was about 2 μm.
[0150] Production Example 2: Production of a hard coat layer-forming composition
[0151] A hard coat layer-forming composition was prepared by mixing 16.2 g of a dendrimer compound (SP-1106, Miyoshi Specialty Chemicals Co., Ltd.), 14.4 g of inorganic nanoparticles (10 to 20 nm, silica particles: 50% by weight, solvent: methyl ethyl ketone (MEK)), 1.8 g of a polyfunctional (meth)acrylate compound containing an ethylene glycol group, 0.7 g of a photoinitiator 1-hydroxycyclohexyl phenyl ketone, and 2.9 g of methyl ethyl ketone.
[0152] Manufacturing Example 3: Preparation of hard coating
[0153] The hard coating thickness after curing was calculated by adjusting the type of Mayer bar and the solid content. The composition for forming a hard coating layer prepared in the above-mentioned Preparation Example 2 was bar-coated on one side of the upper polarizing plate and the lower polarizing plate prepared in the Preparation Example 1. After drying at 80° C. for 5 minutes, the composition was heated at 500 mJ / cm2 in a high-pressure mercury lamp. 2 The upper polarizing plate and the lower polarizing plate each having a hard coating layer formed on one surface are cured by curing with a light intensity of , thereby respectively manufacturing the upper polarizing plate and the lower polarizing plate. The hard coating layer has a Vickers hardness of 40 after drying and a thickness of about 8 to 12 μm.
[0154] Manufacturing Example 4: Preparation of Transparent Conductive Layer
[0155] Place the upper polarizing plate and the lower polarizing plate prepared in the above-mentioned manufacturing example 3, apply a 450W DC power supply to start the sputtering gun, and then induce plasma to the ITO (10wt% Sn doped (doped) In2O3) target, thereby forming a transparent conductive layer (90nm) on the hard coating layer of the upper polarizing plate and the lower polarizing plate. Start the ion gun with a 50WDC power to perform ion treatment on the transparent conductive layer formed above. At this time, the pressure is maintained at 3mTorr at room temperature and argon and oxygen are supplied at 30sccm and 1sccm respectively. At this time, the ITO thickness is measured by FT-SEM, and the ITO surface resistance (Ω / □) is measured using a four-point probe.
[0156] Manufacturing Example 5: Orientation Film Preparation
[0157] The alignment liquid was applied to the ITO surface of the upper polarizing plate and the lower polarizing plate prepared in the above-mentioned manufacturing example 4 and dried (80°C / 2 minutes). Then, UV was irradiated on the above-mentioned dried alignment liquid to form an alignment film, thereby respectively preparing an upper polarizing plate stack (i.e., a first stack) and a lower polarizing plate stack (i.e., a second stack).
[0158] Production Example 6: Preparation of Optical Layered Body b-1
[0159] After forming a PEDOT electrode layer (DaeHa ManTech Co., Ltd.) on the hard coating layer of the upper polarizer and the lower polarizer, ITO was formed on the above PEDOT electrode layer. In addition, an upper polarizer laminated body having an upper polarizer / hard coating layer / PEDOT / ITO / alignment film laminated in this order and a lower polarizer laminated body having a lower polarizer / hard coating layer / PEDOT / ITO / alignment film laminated in this order were prepared according to the above Manufacturing Examples 1 to 5. Then, a spacer was mixed with 100 ml of IPA as a reference to prepare a mixed solvent. The mixed solvent manufactured above is placed in a spacer dispenser (SDSS-KHU02, Shinto Giken Co., Ltd.), spread on the lower polarizing plate stack at 110°C and then dried for 20 minutes to form a spacer on the orientation film of the lower polarizing plate stack. Then, a frame sealant applicator (SHOTmini200Ωx, MUSASHI Co., Ltd.) is used to apply frame sealant (UVF-006, 70,000 mPa·s, SEKISUI Co., Ltd.) on the outer peripheral surface of the lower polarizing plate stack according to the product size. Then, in a state where the polarization axes of the upper polarizing plate and the lower polarizing plate are arranged parallel to each other at 0° or 90°, dispersed liquid crystal is injected into the orientation film of the upper polarizing plate stack by a One Drop Filling (ODF) process. Then, the upper polarizing plate stack and the lower polarizing plate stack are placed at 3Kg / cm 2 After pressure bonding, UV curing (500mJ / cm 2 ), thereby producing an optical laminate b-1 for smart windows.
[0160] Production Example 7: Preparation of Optical Layered Body b-2
[0161] According to the above manufacturing examples 1 to 5, an upper polarizing plate laminated body with an upper polarizing plate / hard coating / ITO / orientation film laminated in sequence and a lower polarizing plate laminated body with a lower polarizing plate / hard coating / ITO / orientation film laminated in sequence were respectively manufactured, and a spacer was mixed with IPA 100ml as a reference to manufacture a mixed solvent. Then, the above-made mixed solvent was placed in a spacer dispenser (SDSS-KHU02, Shinto Giken Co., Ltd.), spread on the lower polarizing plate laminated body at 110°C and dried for 20 minutes, and a spacer was formed on the orientation film of the above-mentioned lower polarizing plate laminated body, and then a frame sealant (UVF-006, 70,000 mPa·s, Sekisui Co., Ltd.) was applied on the outer peripheral surface of the above-mentioned lower polarizing plate laminated body using a frame sealant dispenser (SHOTmini 200Ωx, Musashi Co., Ltd.) according to the product size. Then, dispersed liquid crystal was injected into the alignment film of the upper polarizing plate stack by ODF process, with the polarization axes of the upper polarizing plate and the lower polarizing plate parallel to each other at 0° or 90°. 2 After pressure bonding, UV curing (500mJ / cm 2 ), thereby manufacturing an optical laminate b-2 for smart windows.
[0162] Production Example 8: Preparation of Optical Layered Body b-3
[0163] According to the above manufacturing examples 1, 4 and 5, an upper polarizing plate laminated body in which an upper polarizing plate / ITO / orientation film is stacked in sequence and a lower polarizing plate laminated body in which a lower polarizing plate / ITO / orientation film is stacked in sequence are respectively manufactured. First, a mixed solvent is manufactured by mixing a spacer based on 100ml of IPA. Then, the mixed solvent manufactured above is placed in a spacer dispenser (SDSS-KHU02, Shinto Giken Co., Ltd.), spread on the lower polarizing plate laminated body at 110°C and dried for 20 minutes, and a spacer is formed on the orientation film of the above lower polarizing plate laminated body. After that, a frame sealant (UVF-006, 70,000 mPa·s, Sekisui Co., Ltd.) is applied on the outer peripheral surface of the above lower polarizing plate laminated body using a frame sealant applicator (SHOTmini 200Ωx, Musashi Co., Ltd.) according to the product size. Then, dispersed liquid crystal was injected into the orientation film of the upper polarizer stack by ODF process, with the polarization axes of the upper polarizer and the lower polarizer parallel to each other at 0° or 90°. 2 After pressure bonding, UV curing (500mJ / cm 2 ), thereby producing an optical laminate b-3 for smart windows.
[0164] Examples and Comparative Examples
[0165] Optical layered bodies of Examples 1 to 8 and Comparative Examples 1 to 5 were prepared according to the types and contents of the spacers and the types of the optical layered bodies shown in Tables 1 and 2 below, respectively.
[0166] [Table 1]
[0167]
[0168]
[0169] [Table 2]
[0170]
[0171] -a-1: EZ3P-020 (Sekisui Corporation)
[0172] -a-2: SP-205 (Sekisui Corporation)
[0173] -a-3: EX-005 (Sekisui Corporation)
[0174] -a-4: EXH-005 (Sekisui Corporation)
[0175] -a-5: KBN-505 (Sekisui Corporation)
[0176] -a-6: SI (Sekisui Corporation)
[0177] -b-1: Optical laminate of Production Example 6 -b-2: Optical laminate of Production Example 7 -b-3: Optical laminate of Production Example 8 Experimental example
[0178] (1) Compression elastic modulus ratio
[0179] The compressive elastic modulus of the spacers a-1 to a-6 was measured in accordance with JIS K7208, a compression test method for plastics, and is a value calculated from the 10% K value of 3 μm particles using a nano indenter.
[0180] In addition, the compressive elastic modulus of the upper and lower polarizing plate stacks was measured using the Vickers tip of a nanoindenter (HM500, Fisher). At this time, the hardness of the substrate was measured by loading at a maximum load of 100 mN from 0 mN to 100 mN over 12 seconds, holding for 5 seconds, and then unloading at a rate of 100 mN to 0 mN over 12 seconds.
[0181] Then, the ratio of the compressive elastic modulus of the spacer to the compressive elastic modulus of the upper (and / or lower) polarizing plate laminate was calculated. The results are shown in Tables 1 and 2 above.
[0182] (2) Crack evaluation
[0183] A 10 mm mandrel was used in a cylindrical mandrel bending tester COAD.711, and an optical microscope (OLYMPUS, MX61) was used to confirm whether cracks occurred on the surface of the optical laminate. Specifically, an optical microscope was used and magnified at 10 times the zoom to confirm the cross section of the substrate in contact with the spacer. The results based on the following evaluation criteria are shown in Tables 1 and 2 above.
[0184] <Evaluation Criteria>
[0185] ○: No cracks
[0186] X: Cracks
[0187] (3) Substrate contact evaluation
[0188] Similar to the above crack evaluation, a 10 mm mandrel was used in a cylindrical mandrel bending tester COAD.711 and an optical microscope (Olympus, MX61) was used to check whether the upper polarizing plate stack and the lower polarizing plate stack were in contact at the bend. The results based on the following evaluation criteria are shown in Tables 1 and 2 above.
[0189] <Evaluation Criteria>
[0190] ○: Confirm light transmission
[0191] X: Black spots are visible
[0192] Referring to Table 1 above, from the bending evaluation results of the optical stacks of Examples 1 to 8 in which the ratio of the compressive elastic modulus of the spacer to the compressive elastic modulus of the upper and lower polarizing plate stacks is 0.75 to 1.55 and the content of the spacer relative to the total weight of the dispersed liquid crystal is 0.5 to 3.0 weight %, it can be seen that not only does the substrate of the optical stack, especially the substrate in contact with the spacer, not produce cracks, but also the upper polarizing plate stack and the lower polarizing plate stack in the bent portion are not in contact, so the light transmittance is good.
[0193] On the other hand, referring to the above Table 2, in the case of the optical laminates of Comparative Examples 1 to 3, although the content of the spacer relative to the total weight of the dispersed liquid crystal satisfies 0.5 to 3.0 weight %, the ratio of the compressive elastic modulus of the spacer to the compressive elastic modulus of the upper and lower polarizing plate stacks does not satisfy 0.75 to 1.55, based on the bending evaluation results, it can be seen that cracks are generated in the substrate of the optical laminate, especially the substrate in contact with the spacer (Comparative Examples 2 and 3), or the upper polarizing plate stack and the lower polarizing plate stack are in contact at the bent portion and black spots are visible in the corresponding area (Comparative Example 1).
[0194] In addition, referring to the above Table 2, in the case of the optical stacks of Comparative Examples 4 and 5 where the ratio of the compressive elastic modulus of the spacer to the compressive elastic modulus of the upper and lower polarizing plate stacks satisfies 0.75 to 1.55, but the content of the spacer relative to the total weight of the dispersed liquid crystal does not satisfy 0.5 to 3.0 weight %, according to the bending evaluation results, cracks are generated in the substrate of the optical stack, especially the substrate in contact with the spacer (Comparative Example 5), or the upper polarizing plate stack and the lower polarizing plate stack in the bent portion are in contact and black spots are visible in the corresponding area (Comparative Example 4).
[0195] Therefore, it can be seen that the optical laminate of the present invention, in which the ratio of the compressive elastic modulus of the spacer to the compressive elastic modulus of the upper and / or lower polarizing plate stack satisfies 0.75 to 1.55 and the content of the spacer relative to the total weight of the dispersed liquid crystal satisfies 0.5 to 3.0 weight %, not only has excellent bending characteristics, but also has excellent light transmittance due to the ease of ensuring liquid crystal space.
[0196] Industrial Applicability
[0197] According to the variable transmittance optical stack of the present invention, when the ratio of the compressive elastic modulus of the above-mentioned spacer to the compressive elastic modulus of any one of the first stack and the second stack satisfies 0.75 to 1.55 and the spacer content relative to the total weight of the dispersed liquid crystal satisfies 0.5 to 3.0 weight %, an optical stack that does not generate cracks and has excellent durability can be provided.
Claims
1. A variable transmittance optical stack, comprising: A first stacked body, which is sequentially stacked with a first polarizing plate, a first transparent conductive layer and a first alignment film; A second laminated body including a second polarizing plate, a second transparent conductive layer, and a second alignment film laminated in this order; and dispersed liquid crystal, which is arranged between the first stack and the second stack, The dispersed liquid crystal includes a spacer, The ratio of the compressive elastic modulus of the spacer to the compressive elastic modulus of any one of the first stack and the second stack is 0.75 to 1.55, The content of the spacer is 0.5 to 3.0 weight % relative to the total weight of the dispersed liquid crystal. 2 . The variable transmittance optical stack according to claim 1 , wherein a compressive elastic modulus of any one of the first stack and the second stack is 3,000 to 4,000 MPa. 3 . The variable transmittance optical stack according to claim 1 , wherein the compressive elastic modulus of the spacer is 2,000 to 5,500 MPa. 4 . The variable transmittance optical stack according to claim 1 , wherein the spacer includes at least one selected from the group consisting of spherical spacers and columnar spacers. 5 . The variable transmittance optical laminate according to claim 1 , wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed to be in direct contact with one of the first polarizing plate and the second polarizing plate.
6. The variable transmittance optical stack according to claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer comprises one or more selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires. 7 . The variable transmittance optical stack according to claim 1 , wherein at least one of the first polarizing plate and the second polarizing plate comprises one or more selected from the group consisting of a functional coating layer, a protective layer, a phase difference adjusting layer, a refractive index adjusting layer and an overcoat layer. 8 . The variable transmittance optical laminate according to claim 1 , wherein at least one of the first polarizing plate and the second polarizing plate has a thickness of 30 to 200 μm. 9 . The variable transmittance optical stack according to claim 1 , comprising a frame sealant disposed between the first stack and the second stack. 10 . The variable transmittance optical stack according to claim 1 , further comprising at least one selected from the group consisting of a sticking / adhesive layer, a UV absorbing layer, and an impact-resistant layer. 11 . The method for producing the variable transmittance optical layered body according to claim 1 . 12 . A smart window comprising the variable transmittance optical laminate according to claim 1 .
13. A vehicle comprising the smart window according to claim 12.
14. An automobile, wherein the smart window according to claim 12 is applied to at least one of a front window, a rear window, a side window, a skylight, and an interior partition.
15. A wearable device comprising the smart window according to claim 12.
16. A building window, comprising the smart window according to claim 12.